2013
DOI: 10.1902/jop.2012.120076
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Periodontal Destruction and the Roles of Advanced Glycation End Products in Experimental Diabetes

Abstract: Diabetes augments periodontal destruction by reducing the proliferating capability and activating resorptive activities. Presence of the AGE-RAGE axis without diabetes implies that it is involved in the regulation of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 42 publications
7
64
0
1
Order By: Relevance
“…The down-regulation of TNF-α (Fig. 4C) also confirmed that the activation of the AGE-RAGE axis was in parallel with the progression of inflammation (Chang et al, 2012(Chang et al, , 2013. However, without the infection from exogenous pathogens, inflammation was elicited only in the initial stages and gradually receded in the control group (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…The down-regulation of TNF-α (Fig. 4C) also confirmed that the activation of the AGE-RAGE axis was in parallel with the progression of inflammation (Chang et al, 2012(Chang et al, , 2013. However, without the infection from exogenous pathogens, inflammation was elicited only in the initial stages and gradually receded in the control group (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, the beneficial effects of RAGE blockade were paralleled by suppressed expression of the receptor and its ligands in gingival tissues and were independent of the level of glycaemia. Increased RAGE expression was subsequently reported in other experimental models of diabetes-associated periodontitis (Chang et al 2012a,b, Claudino et al 2012) and in gingival tissues of diabetic individuals with periodontitis, and its expression was correlated to that of NF-kB (Katz et al 2005, Abbass et al 2012, Yu et al 2012. These findings demonstrated that AGE-RAGE interaction may lead to the exaggerated inflammatory response and periodontal tissue destruction seen in diabetes.…”
Section: Hyperglycaemia and Cellular Stressmentioning
confidence: 66%
“…Research indicates that T2DM has been associated with the formation and accumulation of advanced glycation end products (AGEs), which contribute to its pathogenesis and to abnormal periodontal wound healing. 6,7 These end products reduce the production of matrix proteins such as collagen and osteocalcin by gingival and periodontal fibroblasts. 8 It has also been suggested that T2DM patients present with persistent inflammatory response, significant attachment loss, and increased alveolar bone resorption.…”
Section: Introductionmentioning
confidence: 99%